Legal Study of Anti-Monopoly Activities and Fair Business Competition in the Business World - Pijoh, Feibe Engeline; Melo, Isye Junita; Hs., Fatimah; Adama, Nabila Azizah (Technium Social Sciences Journal, 2023)
The goal of this study is The purpose of this writing is to learn about the law of fair business competition, as well as to understand the legal rules against monopoly activities and unfair business competition in the business world, while the benefits that can be obtained from the results of this research are beneficial for practitioners of law, particularly in the legal regulation of business competition in companies, and can be used as study material for legal arrangements in the event of monopoly activities and unfair business competition. The author defines the issue as follows: What is the objective of fair business competition legislation, and what are the legal regulations in the business sector against monopolistic activities and unfair business competition? The study’s findings indicate that in the business world, business rivalry is unavoidable; in order for products and businesses to exist, organizations must fight to gain the market. Business rivalry is an unavoidable need at this time, owing to the rising number of firms that have been founded and the more aggressive management of corporations in marketing their products to the market in order to increase profits. The goal of business competition law is to ensure that an economy is based on business competition, with the assumption that through fair business competition, producers will strive to achieve consumer satisfaction through quality products, low prices, and the use of the fewest production resources possible.